Pemanfaatan Media Komunikasi Terhadap Optimalisasi Kinerja Kepala Lembang Balla Di Masa Pandemi - Rahelda Nopsa (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: There are complaints from the community in Lembang Limbong Sangpolo in receiving services, so this study aims to determine the index of community satisfaction with leadership and public service in Lembang Limbong Sangpolo, Kurra District, Tana Toraja Regency. The research method used in this study is descriptive quantitative, a sample of 150 people, using accidental sampling technique, collecting data using questionnaires and observing a predetermined sample. The results of the study based on 14 indicators have varied values ​​with the highest assessment being on the certainty of service fees 3.35 and the lowest assessment on completion time2.74, with a weighted average 3.17 IKM conversion value 79.25 so that quality is obtained service (B) which is included in the